1971
DOI: 10.1063/1.1660195
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Study of Faulting in BCC Metals and Alloys

Abstract: Faulting on {211} planes has been reported in filings of many bcc materials based on differences in the broadening of various peaks in the x-ray powder pattern. These experiments have been repeated in this work using (a) recent techniques for correcting for various experimental errors and (b) new derivations of effects of faults on other planes. It is shown that the mean-square strains 〈εL2〉 are generally inversely proportional to the distance L normal to the reflection planes. As a result, it is possible to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…A nearly perfect hyperbolic trend in the (eZ(L)> vs L plot has been obtained, and this is paralleled by a nearly perfectly linear trend in the VHH plot, where In[T(L,n)/T(L,n+ 1)] vs L is recorded. This behaviour can be interpreted as due to the presence of 'intracrystalline' disorder (Rothman & Cohen, 1971;Crist & Cohen, 1979) caused by dislocations inside each crystallite or to 'paracrystallinity' according to Hosemann's theory (Hosemann & Bagchi, 1962). In the present case no physical reason can justify the presence of paracrystallinity.…”
Section: Fourier Methodsmentioning
confidence: 99%
“…A nearly perfect hyperbolic trend in the (eZ(L)> vs L plot has been obtained, and this is paralleled by a nearly perfectly linear trend in the VHH plot, where In[T(L,n)/T(L,n+ 1)] vs L is recorded. This behaviour can be interpreted as due to the presence of 'intracrystalline' disorder (Rothman & Cohen, 1971;Crist & Cohen, 1979) caused by dislocations inside each crystallite or to 'paracrystallinity' according to Hosemann's theory (Hosemann & Bagchi, 1962). In the present case no physical reason can justify the presence of paracrystallinity.…”
Section: Fourier Methodsmentioning
confidence: 99%
“…(15) Then (5) is used to calculate <e2> 1/2 the r.m.s, micro-50, strain averaged over L = 50 A. This latter step assumes that the strains obey a hyperbolic law which has been well established in metals (Rothman & Cohen, 1969, 1971. The significant point is that the initial-slope method gives results which are clearly more accurate than those from the more elaborate single-peak analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The reduced mean-square displacement (Z 2) can be written in terms of microstrain (e, 2) with (1). Rothman & Cohen (1969, 1971 have shown theoretically and experimentally that for cold-worked metals…”
Section: (2)mentioning
confidence: 99%
“…For small n, A~ ~-1-na3/Dhu. Also, it has been shown (Rothman & Cohen, 1971) that (e2)~-G2/na3, where G is a constant. Substituting these relationships into (1), Mignot & Rondot (1975) showed that {a3 t ) +n2~ 2rc2a2G2 [ d2klDeff or (4) A.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses are carried out on a sin 0 scale. The 'hook' effect (the decrease in Fourier coefficients at very low harmonic number) is minimized following Rothman & Cohen (1971). In the case of multiple peaks, the cosine expansion (Delhez & Mittemeijer, 1976) is used to separate crystallite size and strain terms in place of the traditional but less-accurate logarithmic expansion.…”
Section: Introductionmentioning
confidence: 99%